The effect of tourism activities towards natural resource conservation in Kilim Karst Geoforest Park, Langkawi - Widad Mohd Ismail (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Tourism is one of the key sector that generate income to Malaysia economic. Therefore, LADA had made great effort in positioning Langkawi Island on the list of United Nations Educational, Scientific and Cultural Organisation (UNESCO) as one of a recognized Geopark in June, 2007. The international acknowledgment from UNESCO, raised Langkawi Geopark to the eyes of the world as one of the conserved geological heritage area. Nevertheless, it has been reported in 2014, the island had received a warning card due to conservation issues. The incident could affect the Geopark status of the island. This complications might caused by numerous factors including the excessiveness of tourism activities. Therefore this study aims to ascertain type of tourism activities that affected natural resource conservation. The focus area is in Kilim Karst Geoforest Park, Langkawi. Several problems have been identified such as 1) tourism activities increased pollution along Kilim waterways, 2) tourism activities affect nature and wildlife habitat in Kilim, 3) also high capacity and frequency of tourists arrivals affected bat habitat and natural heritage in Bat Cave. Meanwhile, the research objectives are 1) to study type of tourism activities that increased pollution along Kilim waterways, 2) to recognize factor that affected nature and wildlife habitat in Kilim 3) and to ascertain form of human interference that affected bat habitat and natural heritage in Bat Cave. Data were obtained from structured questionnaires, semi-structured interviews and observations. All respondents were selected from local residents, staffs involved in Kilim tourism and tourists. Then, all data were analyzed using SPSS software into descriptive and one-way anova analysis. Most problematical questions received the highest score with extremely agree in likert scale survey by respondents. This proved most of the respondents witnessed the conservation issues in Kilim Karst Geoforest Park. Hence, in order to conserve the area for future generations as well as to be continuously recognized by UNESCO, all parties involved in Kilim Karst Geoforest Park tourism including staff, local residents and tourists should take responsibility in conserving the valuable natural resources. Keywords: Kilim Karst Geoforest Park, recognition, tourism activities, conservation, natural resources.